Correlation and causality: a COVID-19 conundrum. Issue 4 (15th October 2020) - Morice, Alyn H.
I read with interest the two contributions by J.D. Chalmers and co-workers to the July issue of the European Respiratory Journal . In a reply to correspondence concerning the inhaled corticosteroid withdrawal controversy in COPD [1], they suggest that A. Agusti succumbs to the fallacy of post hoc, ergo, propter hoc [2], i.e. A occurred, then B occurred: therefore, A caused B. However, as we know, correlation is not causality. Predictive models depend heavily on the assumptions made in their construction https://bit.ly/2Eex05F